A brand foci model to explain achievement needs: a contradictory explanation. Issue 4 (11th September 2017) - Sierra, Jeremy J.; Taute, Harry A.; Lee, Byung-Kwan
Abstract : Purpose: The purpose of this paper is to explore the indirect effect of smartphone-brand tribalism on the need for achievement. Design/methodology/approach: Using survey data from 272 South Korean respondents, path analysis is used to evaluate the hypotheses. Findings: Only the sense of community dimension of brand tribalism affects brand pride (PRIDE ), which in turn leads to a sequential process of brand attitude, purchase intention, and need for achievement (NACHIEVE ). Research limitations/implications: South Korean data may confine generalizability. As effect sizes in this context are understood, researchers have an additional benchmark for future brand tribalism and PRIDE research. Practical implications: The psychological underpinning and, the presence of brand tribes in society cannot be overlooked by strategists. Such tribal-laden following is also evident within smartphone communities. By further understanding brand tribalism outcomes, marketers and brand leaders are in an improved position to develop strategies that appeal to targeted customers, ultimately growing and strengthening their brand tribes. Originality/value: Supported by the anthropological view of brand tribalism, this research contributes to the branding literature by examining the indirect effects of brand tribalism on the NACHIEVE through brand-related attitudes and behavioral intentions. Where previous research using westerners indicates the explanatory power of defense of the tribe on brand-related factors, no effect in this regard is found here using eastern smartphone consumers.